# Thread: Can I simplify the following function

1. ## Can I simplify the following function

Can I simplify $\int \frac {e^t}{e^t+1}dt$ into $\int 1+e^t dt$

so that the antiderivative will be $x+e^t+C$

2. Originally Posted by cammywhite
Can I simplify $\int \frac {e^t}{e^t+1}dt$ into $\int 1+e^t dt$

so that the antiderivative will be $x+e^t+C$
um, no. this is a substitution problem. let $u = 1 + e^t$

3. Originally Posted by cammywhite
Can I simplify $\int \frac {e^t}{e^t+1}dt$ into $\int 1+e^t dt$

so that the antiderivative will be $x+e^t+C$
No.

Use substitution. Let $u = e^t + 1$

$\frac{du}{dt} = e^t$

$du = e^t dt$

Therefore integral becomes:

$\int \frac{du}{u}$

4. Originally Posted by Mush
No.

Use substitution. Let $u = e^t + 1$

$\frac{du}{dt} = e^t$

$du = e^t dt$

Therefore integral becomes:

$\int \frac{du}{u}$
so it will be $\frac {e^t+x}{e^t+1}$

5. *sigh* please review your integration rules: $\int \frac 1x~dx = \ln |x| + C$

6. Originally Posted by Jhevon
*sigh* please review your integration rules: $\int \frac 1x~dx = \ln |x| + C$
I just have problem with the substituting part...

Let $u=e^t+1$

so $\int \frac {e^t}{e^t+1}dt$ will equal to $\int \frac {u-1}{u}dt$

am i correct???

7. Originally Posted by cammywhite
I just have problem with the substituting part...

Let $u=e^t+1$

so $\int \frac {e^t}{e^t+1}dt$ will equal to $\int \frac {u-1}{u}dt$

am i correct???

picking up where Mush left off: we have

$\int \frac 1u~du$

applying the rule i just gave you, we get

$\ln |u| + C$

now back-substitute for $u$, we get:

$\ln |e^t + 1| + C$

8. Maybe some colour would help.

${\color{red}u = e^t + 1} \ \Rightarrow \ {\color{blue}du = e^t dt}$

So your integral: $\int \frac{{\color{blue}e^t dt}}{{\color{red}e^t + 1}} = \int \frac{{\color{blue}du}}{{\color{red}u}}$

which is a standard one.

9. Originally Posted by Jhevon

picking up where Mush left off: we have

$\int \frac 1u~du$

applying the rule i just gave you, we get

$\ln |u| + C$

now back-substitute for $u$, we get:

$\ln |e^t + 1| + C$

So in otherwords the derivative of $\ln |e^t + 1| + C$ is $\frac {e^t}{e^t+1}?$
So in otherwords the derivative of $\ln |e^t + 1| + C$ is $\frac {e^t}{e^t+1}?$
yes. by the chain rule: $\frac d{dx} \ln u = \frac {u'}u$